A convergência entre o pensamento de marketing e as abordagens administrativas: fundamentos teóricos da interdependência entre o marketing de conteúdo e o inbound marketing - Palos, Carlos Alberto Noronha (2025)
This article aims to analyze the convergence between marketing thinking and administrative approaches, reinforcing the theoretical foundations of the interdependence between Content Marketing and Inbound Marketing. It proposes a formal analysis of marketing oriented towards relationships and enchantment, addressing its historical origins based on administrative pre-cepts, the evolution of marketing thinking, as well as its foundations and practical implications for the contemporary organizational environment. The research adopts an exploratory and qua-litative methodology, based on a bibliographical review of classic and contemporary marketing authors, such as Cobra, Kotler, Bartels, Pulizzi, Avis, Gabriel and Steffen, as well as studies on the transformation of marketing, administrative approaches and permission marketing. The study is structured into five chapters that range from the evolution of marketing thinking to future content trends in digital marketing. The results indicate that the evolution of marketing is presented through administrative, technological, social and marketing development and Con-tent Marketing is the cause and consequence of this process and also an essential tool for ope-rationalizing the stages of Inbound Marketing. It was found that both approaches share concep-tual bases. However, effective integration between content and inbound still faces challenges and limitations. It is concluded that understanding this interdependence, based on the historical construction of marketing, is fundamental both for the theoretical advancement of the field and for its strategic application in organizations, offering guidelines that allow technology, creati-vity and relationships to be aligned in a digital scenario in constant transformation.